Crystallization and preliminary crystallographic analysis of a surface antigen glycoprotein, SAG19, from Eimeria tenella. Issue 12 (1st December 2013) - Ramly, Nur Zazarina; Rouzheinikov, Sergey N.; Sedelnikova, Svetlana E.; Baker, Patrick J.; Chow, Yock‐Ping; Wan, Kiew‐Lian; Nathan, Sheila; Rice, David W.
<x xml:space="preserve">Abstract</x> Coccidiosis in chickens is caused by the apicomplexan parasite Eimeria tenella and is thought to involve a role for a superfamily of more than 20 cysteine‐rich surface antigen glycoproteins (SAGs) in host–parasite interactions. A representative member of the family, SAG19, has been overexpressed in Escherichia coli, purified and crystallized by the hanging‐drop method of vapour diffusion using ammonium sulfate as the precipitant. Crystals of SAG19 diffracted to beyond 1.50 Å resolution and belonged to space group I4, with unit‐cell parameters a = b = 108.2, c = 37.5 Å. Calculation of possible values of VM suggests that there is a single molecule in the asymmetric unit.